Aktivitas Antioksidan dari Ekstrak Daun Kedondong (Spondias dulcis) Melalui Penangkal Radikal Superoksida - Somantri, Ucu Wandi; Rudiana, Tarso; Kuncoroyekti, Prasetyo Alfaridzi (Jurnal Kartika Kimia, 2022)
Ambarella (Spondias dulcis) is a tropical plant which is known to have antioxidant activity. This study aims to determine the antioxidant activity of the n-hexane, ethyl acetate and methanol extracts of S. dulcis leaves through superoxide radical scavenging and to characterize the phytochemical compounds in the extract using LCMS/MS. S. dulcis leaf powder was macerated with n-hexane, ethyl acetate and methanol. Antioxidant activity was tested through superoxide radical scavengers. The n-hexane extract of S. dulcis leaves had the best antioxidant activity with an IC50 value of 2080 µg/mL. Based on LCMS/MS, 6 compounds were detected in the n-hexane extract at retention time (Rt) 3.23-9.89 minutes. Compounds Ajmalin, Scopoletin, scoparone, 3-methyl-6-[[2-(2-methylbut-3-en-2-yl)-1H-indole-3-yl] methyldene]piperazine-2,5-dione, [3-hydroxy-3-methylbut-1-enyl]-5,7-dimethoxy-2-phenyl-2,3-dihydrochromene-4-one, and 4-hydroxy-3-(3-methylbut-2-enyl)phenyl ]ethanone.